A metasynthesis of qualitative studies regarding opinions and perceptions about barriers and determinants of health services' accessibility in economic migrants - Agudelo-Suárez Andrés A; Gil-González Diana; Vives-Cases Carmen; Love John G; Wimpenny Peter; Ronda-Pérez Elena (BMC, 2012)
Abstract Background Access to health services is an important health determinant. New research in health equity is required, especially amongst economic migrants from developing countries. Studies conducted on the use of health services by migrant populations highlight existing gaps in understanding which factors affect access to these services from a qualitative perspective. We aim to describe the views of the migrants regarding barriers and determinants of access to health services in the international literature (1997-2011). Methods A systematic review was conducted for Qualitative research papers (English/Spanish) published in 13 electronic databases. A selection of articles that accomplished the inclusion criteria and a quality evaluation of the studies were carried out. The findings of the selected studies were synthesised by means of metasynthesis using different analysis categories according to Andersen's conceptual framework of access and use of health services and by incorporating other emergent categories. Results We located 3,025 titles, 36 studies achieved the inclusion criteria. After quality evaluation, 28 articles were definitively synthesised. 12 studies (46.2%) were carried out in the U.S and 11 studies (42.3%) dealt with primary care services. The participating population varied depending mainly on type of host country. Barriers were described, such as the lack of communication between health services providers and migrants, due to idiomatic difficulties and cultural differences. Other barriers were linked to the economic system, the health service characteristics and the legislation in each country. This situation has consequences for the lack of health control by migrants and their social vulnerability. Conclusions Economic migrants faced individual and structural barriers to the health services in host countries, especially those with undocumented situation and those experimented idiomatic difficulties. Strategies to improve the structures of health systems and social policies are needed.